Specificity in Rehabilitation of Word Production: A Meta-Analysis and a Case Study - Charlotte Jacquemot; Emmanuel Dupoux; Laura Robotham; Anne-Catherine Bachoud-Lévi (Behavioural Neurology)
Speech production impairment is a frequent deficit observed in aphasic patients and rehabilitation programs have been extensively developed. Nevertheless, there is still no agreement on the type of rehabilitation that yields the most successful outcomes. Here, we ran a detailed meta-analysis of 39 studies of word production rehabilitation involving 124 patients. We used a model-driven approach for analyzing each rehabilitation task by identifying which levels of our model each task tapped into. We found that (1) all rehabilitation tasks are not equally efficient and the most efficient ones involved the activation of the two levels of the word production system: the phonological output lexicon and the phonological output, and (2) the activation of the speech perception system as it occurs in many tasks used in rehabilitation is not successful in rehabilitating word production. In this meta-analysis, the effect of the activation of the phonological output lexicon and the phonological output cannot be assessed separately. We further conducted a rehabilitation study with DPI, a patient who suffers from a damage of the phonological output lexicon. Our results confirm that rehabilitation is more efficient, in terms of time and performance, when specifically addressing the impaired level of word production.